2010
DOI: 10.1097/jnn.0b013e3181e26b1d
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in Older Adults With Alzheimer's Disease

Abstract: Sleep in older adults with Alzheimer's disease can often be extremely fragmented, thus disturbing normal sleepYwake rhythms. This poor-quality sleep is challenging for caregivers and frequently results in admitting older adults to long-term care institutions. Many variables, such as genes, medications, depression, and environmental factors, influence sleep in persons with Alzheimer's disease. Interventions, such as exposure to light, melatonin therapy, sleep hygiene, and physical activity, are commonly used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 83 publications
1
25
0
Order By: Relevance
“…Its therapeutic applications are numerous, from pediatric [49,50,51] to geriatric diseases [52,53,54]; this includes cancer [55,56], sleep disturbances [57,58] and neurodegenerative diseases [59,60]. …”
Section: Why Melatonin?mentioning
confidence: 99%
“…Its therapeutic applications are numerous, from pediatric [49,50,51] to geriatric diseases [52,53,54]; this includes cancer [55,56], sleep disturbances [57,58] and neurodegenerative diseases [59,60]. …”
Section: Why Melatonin?mentioning
confidence: 99%
“…Sleep represents a series of well-defined and behaviorally relevant transitions in neural state that are stable across normal human sleepers while showing distinct changes across the lifespan (Campbell and Murphy, 2007; Gertner et al, 2002; Munch et al, 2010; Terry et al, 2004) and in many neuropathologies (Claassen et al, 2010; Moller et al, 2009; Song et al, 2010; Walters et al, 2008). While a number of studies have examined network correlates of stable NREM (Braun et al, 1997; Czisch et al, 2004; Dang-Vu et al, 2005, 2008; Horovitz et al, 2008, 2009; Kaufmann et al, 2006; Larson-Prior et al, 2009; Nofzinger et al, 2002; Spoormaker et al, 2010) and REM (Braun et al, 1997; He et al, 2008; Magnin et al, 2004; Maquet et al, 1996, 2005; Wehrle et al, 2005, 2007) sleep, far fewer have examined those of the initial transitional stage of sleep (N1; Corsi-Cabrera et al, 2006; Jann et al, 2009; Kjaer et al, 2002; Laufs et al, 2006; Olbrich et al, 2009; Picchioni et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Residents with dementia experience excessive daytime sleepiness, and at night, difficulty falling asleep, increased duration and frequency of awakenings, and disrupted sleep-wake rhythms (Rose & Lorenz, 2010; Song, Dowling, Wallhagen, Lee, & Strawbridge, 2010). Ancoli-Israel et al (1989) have shown that residents with dementia were not totally awake or fully asleep in a single hour during a 24-hr period, and these residents with dementia, on average, fell asleep 22 times for a total of 2 hr during the daytime (Ancoli-Israel, Parker, Sinaee, Fell, & Kripke, 1989).…”
mentioning
confidence: 99%